Regional Determinants Of Road Traffic Accident In Oromia: Analyzing Vehicle - Related Intervention - Efa Dega (My University, 2025)
The regional determinants of road traffic accidents in the Oromia region, has been shown to have issues with particularly regarding vehicle- related problems in Oromia region. This can lead to the causes of death and high injury with the Oromia region being one of the most affected areas. To address this, a comprehensive analysis of road traffic accident was conducted using Microsoft Excel, followed by optimization using Design Expert software. The analysis specifically focused on identifying vehicle-related problems that contribute to these regional determinants of road traffic accidents in the Oromia region. The analysis revealed several key findings regarding vehicle-related problems and their association with road traffic accidents in Oromia. Brake failures are the leading causes (30%), likely due to poor maintenance culture and lack of enforcement. There is also steering problems (30%) often arise from neglected repairs and misalignment, contributing significantly to loss of control. and finally, tires of (25%) are strongly linked to overloading and poor road conditions, increasing blowout risks. Therefore, this structured quantification helps prioritize brake and steering system improvements as the most critical areas for reducing Road traffic accidents in Oromia. The findings highlight the need for targeted interventions to address these problems and reduce occurrence of accident. The results underscore the critical importance of focusing on mechanical failures as primary intervention area. Targeted interventions focusing on vehicle condition, proper loading and maintenance systems can significantly reduce accident rates while supporting the region’s mobility needs and economic development. Brake failure, steering problem and tire system failures contribute significantly to Road traffic accidents in Oromia. Addressing these issues through better maintenances, enforcement, and driver education can reduce preventable accidents. Road traffic accidents in Oromia like in many other regions are often influenced by vehicle mechanical failures, particularly in critical systems such as brakes, tires and steering issues.
Keywords: Brake Systems; Mechanical Failures; Optimization Modeling Oromia; Road Traffic Accidents; Steering Systems; Tire Systems